Search for a fermiophobic Higgs boson in pp collisions at root s=7 TeV - Chatrchyan, S. (2012)
Combined results are reported from searches for a fermiophobic Higgs boson in the gamma gamma, WW, and ZZ decay modes in proton-proton collisions at root s = 7 TeV. The explored Higgs boson mass range is 110-300 GeV. The data sample corresponds to an integrated luminosity of 4.9-5.1 fb(-1). A fermiophobic Higgs boson is excluded at 95% confidence level in the mass range 110-194 GeV, and at 99% confidence level in the mass ranges 110-124.5 GeV, 127-147.5 GeV, and 155-180 GeV.